Calcular sin calculadora, \frac{1}{\cos^{2}(10^{\circ})} + \frac{1}{\sin^{2}(20^{\circ})} + \frac{1}{\sin^{2}(40^{\circ})} - \frac{1}{\cos^{2}(45^{\circ})}
Intento:
Deje A = \cos(10) \sin(20) \sin(40), luego
\frac{1}{\cos^{2}(10)} + \frac{1}{\sin^{2}(20)} + \frac{1}{\sin^{2}(40)} = \frac{\sin^{2}(20) \sin^{2}(40) + \cos^{2}(10) \sin^{2}(40) + \cos^{2}(10) \sin^{2}(20)}{A^{2}} aviso también 2A \sin(10) \sin(40) = \sin^{2}(20) \sin^{2}(40) 2A \cos(20) \cos(10) = \cos^{2}(10) \sin^{2}(40) así tenemos
\frac{2A \sin(10) \sin(40) + 2A \cos(20) \cos(10)+ \cos^{2}(10) \sin^{2}(20)}{A^{2}}
= \frac{2A \left[2 \sin(10) \sin(20) \cos(20) + \frac{\sqrt{3}}{2} + \sin(10)\sin(20) \right]+ \cos^{2}(10) \sin^{2}(20)}{A^{2}}
= \frac{2A \left[\sin(10) \sin(20) (1+ \cos(20) + \cos(20)) + \frac{\sqrt{3}}{2} \right]+ \cos^{2}(10) \sin^{2}(20)}{A^{2}}
= \frac{2A \left[\sin(10) \sin(20) (3\cos^{2}(10) - \sin^{2}(10)) + \frac{\sqrt{3}}{2} \right]+ \cos^{2}(10) \sin^{2}(20)}{A^{2}}
Cómo seguir entonces?